CLASS EXPLOITATION IN RON RASH’S SERENA NOVEL: A MARXIST CRITICISM - Richi Paglinawan; Surya Sili; Fatimah Muhajir (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
This research has examined the marxist feminist and patriarchy as the types and form of female issues based on research questions. By using qualitative method, this research uses qualitative research managed to find the issues that occur in this film about how capitalists and patriarchy create the issues toward women. This research tries to identify the types of woman issues contained in the film Suffragette. This film is directed by Sara Gavron. The Suffragette film was inspired by the true story of a group of women activists led by Emmeline Pankhurst, in fighting for women's rights to political and economic participation. Suffragette tells the story using the perspective of the character of Maud Watts, a laundry service worker who joined Pankhurst in raising the issue of women's rights to vote before Parliament; which allowed mainly for upper class men. This research shows the imbalance of political opportunity between the upper class and lower class the dominance of masculinity over female workers. The values of Marxist Feminism were seen through scenes when the character of Maud Watts  testifies before the court and in the Horse Race scene in which the Suffragette groups protest. The court scene shows opposition from women's labor groups, representing women to fight for equality between men and women.